EVALUASI PENERAPAN NO.108 AKUNTANSI ASURANSI SYARIAH (STUDI KASUS PADA TAFAKUL KELUARGA BANDA ACEH) - Zuhra, Fitria; Bustamam, Bustamam (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2020)
The purpose of this study was to determine how the suitability of the recognition, measurement, presentation and disclosure of sharia insurance accounting in the tafakul banda aceh family. This researt using descriptive statistical analysis or qualitative method. The data obtained trough a direct interview with Mr.Jamaluddin as head of the the tafakul banda aceh family agency.The result of the study show that from the financial statements they made, they revealed that there were investments in tabarru funds, assets, then allowances discussed, financial health, contributions, metc.participants, tabarru funds, investment funds,technical allowances allowances, and asset details of this statement are in accordance with item no.108.